Word skipping as an indicator of individual reading style during literary reading - Myrthe Faber; Marloes Mak; Roel Willems (Bern Open Publishing, 2020)
Decades of research have established that the content of language (e.g. lexical characteristics of words) predicts eye movements during reading. Here we investigate whether there exist individual differences in 'stable' eye movement patterns during narrative reading. We computed Euclidean distances from correlations between gaze durations time courses (word level) across 102 participants who each read three literary narratives in Dutch. The resulting distance matrices were compared between narratives using a Mantel test. The results show that correlations between the scaling matrices of different narratives are relatively weak (r ≤ .11) when missing data points are ignored. However, when including these data points as zero durations (i.e. skipped words), we found significant correlations between stories (r > .51). Word skipping was significantly positively associated with print exposure but not with self-rated attention and story-world absorption, suggesting that more experienced readers are more likely to skip words, and do so in a comparable fashion. We interpret this finding as suggesting that word skipping might be a stable individual eye movement pattern.